Evaluating Financial Inclusion Strategies for Rural Development in Rajasthan (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This study evaluates various financial inclusion strategies and their impact on rural development in Rajasthan. It examines government schemes, banking initiatives, and the role of microfinance institutions in improving financial accessibility. The paper also discusses barriers to financial inclusion and provides recommendations for policy improvements.